2016
DOI: 10.1097/jom.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator Responsiveness and Airflow Limitation Are Associated With Deployment Length in Iraq and Afghanistan Veterans

Abstract: In our sample of post-9/11 veterans, longer deployment lengths were associated with significant bronchodilator responsiveness and a trend toward airflow limitation independent of tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…23,24 Two prospective studies of returning military personnel primarily identified asthma and non-spe-cific airway hyperreactivity as the primary respiratory disorder in their study populations. 3,25 Longer deployments were associated with increased bronchodilator responsiveness, with a trend toward increased air-flow limitation. 25 As part of the 2011 Department of Defense/Veterans Affairs Airborne Hazards workshop on spirometry, the following recommendation was made by Department of Defense representatives and have been confirmed by this study: "Department of Defense policy at present should not require routine surveillance spirometry in all military personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Two prospective studies of returning military personnel primarily identified asthma and non-spe-cific airway hyperreactivity as the primary respiratory disorder in their study populations. 3,25 Longer deployments were associated with increased bronchodilator responsiveness, with a trend toward increased air-flow limitation. 25 As part of the 2011 Department of Defense/Veterans Affairs Airborne Hazards workshop on spirometry, the following recommendation was made by Department of Defense representatives and have been confirmed by this study: "Department of Defense policy at present should not require routine surveillance spirometry in all military personnel.…”
Section: Discussionmentioning
confidence: 99%
“…3,25 Longer deployments were associated with increased bronchodilator responsiveness, with a trend toward increased air-flow limitation. 25 As part of the 2011 Department of Defense/Veterans Affairs Airborne Hazards workshop on spirometry, the following recommendation was made by Department of Defense representatives and have been confirmed by this study: "Department of Defense policy at present should not require routine surveillance spirometry in all military personnel. The burden of evaluating asymptomatic personnel with pulmonary function testing abnormalities would outweigh any benefit from early disease detection.…”
Section: Discussionmentioning
confidence: 99%
“…Among 124 veterans referred for evaluation to the New Jersey (NJ) WRIISC (both with and without respiratory symptoms), 26% had a positive bronchodilator response measured in spirometry. This was positively associated with deployment length, adjusted for smoking history ( 84 ). In a subsequent description of 138 veterans evaluated at the NJ WRIISC, 74.6% had normal pulmonary function, 19.6% had an obstructive deficit, and 5.8% had a restrictive deficit.…”
Section: Findings In Clinical Assessments Of Previously Deployed Milimentioning
confidence: 99%
“…Barth et al suggested an increase in reported respiratory disease with respiratory exposures (eg, exposure to dust, smoke, chemicals, and pollutants) . In studies supporting the development of respiratory disease after deployment, the most commonly cited risk factors were duration of deployment and number of deployments . Other associations include exposure to chemical fires, incineration of human and solid waste, dust storms, and combat smoke …”
Section: Impact On the Lower Respiratory Tractmentioning
confidence: 99%